A Psycholinguistic Cross-Cultural Study of the Concept 'Conflict' in India and Ukraine - Girnyk , Andriy; Krylova-Grek , Yuliya; Khan, Azizuddin (East European Journal of Psycholinguistics, 2021)
The paper presents a comparative study of the semantic field of the concept of conflict in Ukrainian and Indian cultures. The literature review has shown that there has not been any discussion on the abstract general concept of conflict. However, we consider such data exceptionally important for a better understanding of the worldview and cultural differences in diverse countries. Our study aimed to identify cultural features, similarities, and differences in the perception of the concept of conflict by representatives of various cultures. To investigate the way the concept of conflict is perceived, we used a set of methods, including speech activity analysis, free-listing for data gathering and processing, mathematical calculation, systematization, and generalization of results We conducted our study in three phases: at the first stage we gathered data, at the second we processed them, and at the third phase we generalized the findings and drawing conclusions. The students from Kyiv-Mohyla Academy (Ukraine) and Indian Institute of Technology Bombay (India) participated in the research (19-24years old). In general, we got 292 questionnaires. The experiment revealed that the common semantic core of the concept of conflict in Ukrainian and Indian cultures contains seven words: fight, misunderstanding, war, disagreement, quarrel, struggle, aggression. But in contrast to the Ukrainian culture, in India, the associations with the given concept predominantly depict the person’s emotional state (sadness, anger, fear, confusion, and misunderstanding). Participants from India also mention caste discrimination and religious diversity. In Ukraine, the word conflict is much associated with negative interaction (quarrel, aggression, argument, dispute, etc.). Besides, in contrast to the Indian culture, there are no associations with social discrimination and religious diversity. The importance of our findings cannot be stressed too much since they can potentially be used in mediation, social advertising, and international negotiations.